Properties of high-temperature epoxy/DDS resin systems for bonding application. (June 2020) - Zhou, Haoran; Fan, Xupeng; Liu, Changwei; Qu, Chunyan; Yuan, Zhen; Jing, Jiaqi; Tang, Yao; Zhao, Daoxiang; Xiao, Wanbao; Su, Kai
The choice of basic epoxy resin (ER) is especially important for the design of epoxy adhesive formulations. In the present study, performance of several high-temperature ER systems, prepared using 4, 4-diaminodiphenylsulfone as the curing agent by the same curing process, was investigated. The curing behavior was studied by dynamic rheometry and differential scanning calorimetry. The thermal properties of the cured resins were investigated by dynamic thermomechanical analysis, thermomechanical analysis, and thermogravimetric analysis. The peeling properties, mechanical behaviors, and moisture absorptivities of the cured resins were also studied. The results showed traditional diglycidyl ether of bisphenol A epoxy to be insufficient in heat resistance. Naphthalene-based ER and bifunctional cardo ER showed higher glass transition temperature values. However, the processability and adhesive properties may not comply with the application requirements. Biphenyl novolac ER has excellent performance in all aspects, which is suitable for use as a high-temperature adhesive.